(untitled) (World Bulletin of Public Health, 2023)
Recently, given the changes that have occurred due to the COVID 19 pandemic, the developed methods and adequate antibacterial treatment have not been able to provide a good result for the treatment of patients with lung abscess on the background of diabetes mellitus in the post-COVID period. As we know, a lung abscess on the background of diabetes mellitus is much more difficult, and given that the patient has had COVID 19, then in this case the clinical picture will be more complex. The management and treatment of patients with this pathology requires an individual approach and a complex of therapeutic measures.